Environmental enrichment applied with sensory components prevents age-related decline in synaptic dynamics: Evidence from the zebrafish model organism - Karoglu-Eravsar, Elif Tugce; Tuz-Sasik, Melek Umay; Adams, Michelle M. (Experimental gerontology, 2021)
Progression of cognitive decline with or without neurodegeneration varies among elderly subjects. The main aim of the current study was to illuminate the molecular mechanisms that promote and retain successful aging in the context of factors such as environment and gender, both of which alter the resilience of the aging brain. Environmental enrichment (EE) is one intervention that may lead to the maintenance of cognitive processing at older ages in both humans and animal subjects. EE is easily applied to different model organisms, including zebrafish, which show similar age-related molecular and behavioral changes as humans. Global changes in cellular and synaptic markers with respect to age, gender and 4-weeks of EE applied with sensory stimulation were investigated using the zebrafish model organism. Results indicated that EE increases brain weight in an age-dependent manner without affecting general body parameters like body mass index (BMI). Age-related declines in the presynaptic protein synaptophysin, AMPA-type glutamate receptor subunits and a post-mitotic neuronal marker were observed and short-term EE prevents these changes in aged animals, as well as elevates levels of the inhibitory scaffolding protein, gephyrin. Gender-driven alterations were observed in the levels of the glutamate receptor subunits. Oxidative stress markers were significantly increased in the old animals, while exposure to EE did not alter this pattern. These data suggest that EE with sensory stimulation exerts its effects mainly on age-related changes in synaptic dynamics, which likely increase brain resilience through specific cellular mechanisms. Environmental enrichment modulates age-dependent changes occuring in the zebrafish brain. ‘Created with BioRender’. [Display omitted] •Sensory EE increases brain weight at old age without altering BMIs.•The levels of DCAMKL1, SYP and GluR2/3 declines with aging.•EE can prevent the effects of aging on DCAMKL1, SYP, NR2B and GEP levels.•EE can alter the levels of glutamate receptor subunits in a gender-specific manner.•Aging increases oxidative stress markers with no evident modulations of EE.